Dysregulation of circadian rhythms has been reported to be particularly high in bipolar disorder, to evaluate whether this relationship is causal - Chakrabarty, Mousumi; Lahan, Vivekananda (International Journal of Research in Medical Sciences, 2025)
Bipolar disorder is a mental illness characterized by dramatic alterations in mood and has several features which suggest a relationship to the biological clock. In bipolar disorders, there are extreme swings of mood, behavior, motivation and cognitive abilities in the same person. Also sleep and circadian rhythm disruptions are common observation in these patients, both during acute episodes as well as during disease-free periods. A plethora of evidence from various studies, including chronotype studies, studies of sleep-wake cycles, studies estimating neuroendocrine/biochemical markers, genetic studies, studies involving social zeitgebers and life events, pharmacological and therapeutic evidence all show a strong association of circadian disruption and bipolar disorder. There is a necessity of establishing a definite hypothesis in the pathways altered in bipolar disorder for development of novel and effective pharmacotherapy. Once the specific mechanistic pathways have been delineated, it will definitely aid in the discovery of novel treatment modalities.